PENGEMBANGAN TERMINAL AGRIBISNIS VIRTUAL BERBASIS WEB - Arif Imam Suroso; I Gusti Ayu Indira Maharani; Marimin Marimin (School of Business, Bogor Agricultural University (SB-IPB), 2005)
This study was conducted to develop the prototype of web based virtual agribusiness center as an instrument to increase the scope of marketing channel of agribusiness products in Indonesia. Using web engineering approach, this virtual agribusiness center information which conceptually has the same role as wholesaler marketing center was developed and tested using one month data of fruits and vegetables prices in traditonal market. There are tree main components of the system: catalog online, cart, and order tracking. To ensure the quality of the system, the system was tested using Pressman approach and evaluation was done based on its functionality, usability, and reliability .